2022
DOI: 10.1111/gbi.12505
|View full text |Cite
|
Sign up to set email alerts
|

Copper mobilisation from Cu sulphide minerals by methanobactin: Effect of pH, oxygen and natural organic matter

Abstract: Aerobic methane oxidation (MOx) depends critically on the availability of copper (Cu) as a crucial component of the metal centre of particulate methane monooxygenase, one of the main enzymes involved in MOx. Some methanotrophs have developed Cu acquisition strategies, in which they exude Cu-binding ligands termed chalkophores under conditions of low Cu availability. A well-characterised chalkophore is methanobactin (mb), exuded by the microaerophilic methanotroph Methylosinus trichosporium OB3b. Aerobic methan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…Finally, pH influences changes in the soil nutrient content and regulates the nutrient uptake of methanotrophs. One study found that a neutral pH range was the ideal living environment for most methanotrophs (Rushworth et al, 2022). There are two mechanisms by which soil pH can affect the assembly of methanotrophic communities—by directly affecting the growth of methanotrophs or by indirectly influencing plants to form methanotrophic communities (Li, Lijuan, et al, 2023; Martin‐Guay et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, pH influences changes in the soil nutrient content and regulates the nutrient uptake of methanotrophs. One study found that a neutral pH range was the ideal living environment for most methanotrophs (Rushworth et al, 2022). There are two mechanisms by which soil pH can affect the assembly of methanotrophic communities—by directly affecting the growth of methanotrophs or by indirectly influencing plants to form methanotrophic communities (Li, Lijuan, et al, 2023; Martin‐Guay et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In any regard, copper uptake using MBs is an important mechanism for methanotrophs to collect this essential trace element from the environment lack of bioavailable copper. For example, MB-OB3b can extract copper from copper-sulfide minerals typically assumed to be biologically unavailable ( 46 ). Here, we demonstrate that the model methanotroph M. trichosporium OB3b can not only secrete and uptake its own MB but also has developed multiple mechanisms to take up copper in the presence of heterologous methanobactin MB-SB2, including initiating transcription of an alternative TBDT.…”
Section: Discussionmentioning
confidence: 99%
“…Copper is released from rocks by natural weathering processes before precipitating as non-bioavailable secondary minerals such as chalcocite (Cu 2 S) (K spa 6 × 10 −16 ). Under Cu limiting conditions, M. trichosporium OB3b produces chalkophore (methanobactin) [ 3 ] to dissolve Cu mineral phases [ 4 ]. Chalkophores also have affinities beyond Cu including Cd, Co, Fe, Mn, Ni, Zn and Pb, U [ 5 ].…”
Section: Introductionmentioning
confidence: 99%